2021
DOI: 10.1186/s12891-021-04316-3
|View full text |Cite
|
Sign up to set email alerts
|

Does systemic lupus erythematosus increase the risk of complications from total hip arthroplasty?

Abstract: Background Patients with systemic lupus erythematosus are more likely to receive THA than the general population. However, it is controversial whether SLE increases the risk of complications from THA. The purpose of this retrospective study was to reassess the risks from THA in patients with SLE under the management model of enhanced recovery after surgery. Methods Patients with systemic lupus erythematosus diagnosed from December 2011 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Chen et al [ 30 ] found that the disease status of SLE did not significantly increase the risk of perioperative wound infection or PJI by controlling for other confounding factors. This is related to the lower starting preoperative hemoglobin in SLE patients compared to that in the osteoarthritis population as reported [ 14 , 33 ]. And Dorsch [ 34 ] also found that SLE is associated with abnormal platelet aggregation and anticoagulant factor antibodies, thus increasing the risk of perioperative bleeding.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Chen et al [ 30 ] found that the disease status of SLE did not significantly increase the risk of perioperative wound infection or PJI by controlling for other confounding factors. This is related to the lower starting preoperative hemoglobin in SLE patients compared to that in the osteoarthritis population as reported [ 14 , 33 ]. And Dorsch [ 34 ] also found that SLE is associated with abnormal platelet aggregation and anticoagulant factor antibodies, thus increasing the risk of perioperative bleeding.…”
Section: Discussionmentioning
confidence: 92%
“…Demographics and clinical outcomes are summarized in Tables 1 Tables 2 . Among the ten screened citations, seven were the case–control studies [ 7 , 11 , 14 , 15 , 17 , 23 , 24 ], two were retrospective [ 18 , 25 ], and one was cohort studies a study [ 10 ]. A total of 29,573 hips in the SLE group were studied compared to 4,013,027 hips in the non-SLE group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations